Interferon-induced transmembrane protein-3 genetic variant rs12252-C is associated with severe influenza in Chinese individuals. - Zhang, Y; Zhao, Y; Li, N; Peng, Y; Giannoulatou, E; Jin, R; Yan, H; Wu, H; Liu, J; Liu, N; Wang, D; Shu, Y; et al. (Springer Nature, 2013)
The SNP rs12252-C allele alters the function of interferon-induced transmembrane protein-3 increasing the disease severity of influenza virus infection in Caucasians, but the allele is rare. However, rs12252-C is much more common in Han Chinese. Here we report that the CC genotype is found in 69% of Chinese patients with severe pandemic influenza A H1N1/09 virus infection compared with 25% in those with mild infection. Specifically, the CC genotype was estimated to confer a sixfold greater risk for severe infection than the CT and TT genotypes. More importantly, because the risk genotype occurs with such a high frequency, its effect translates to a large population-attributable risk of 54.3% for severe infection in the Chinese population studied compared with 5.4% in Northern Europeans. Interferon-induced transmembrane protein-3 genetic variants could, therefore, have a strong effect of the epidemiology of influenza in China and in people of Chinese descent.